Endospore Appendages: a novel pilus superfamily from the endospores of pathogenic Bacilli. (25th May 2021) - Pradhan, Brajabandhu; Liedtke, Janine; Sleutel, Mike; Lindbäck, Toril; Zegeye, Ephrem Debebe; O´Sullivan, Kristin; Llarena, Ann‐Katrin; Brynildsrud, Ola; Aspholm, Marina; Remaut, Han
Abstract: Bacillus cereus sensu lato is a group of Gram‐positive endospore‐forming bacteria with high ecological diversity. Their endospores are decorated with micrometer‐long appendages of unknown identity and function. Here, we isolate endospore appendages (Enas) from the food poisoning outbreak strain B. cereus NVH 0075‐95 and find proteinaceous fibers of two main morphologies: S‐ and L‐Ena. By using cryoEM and 3D helical reconstruction of S‐Enas, we show these to represent a novel class of Gram‐positive pili. S‐Enas consist of single domain subunits with jellyroll topology that are laterally stacked by β‐sheet augmentation. S‐Enas are longitudinally stabilized by disulfide bonding through N‐terminal connector peptides that bridge the helical turns. Together, this results in flexible pili that are highly resistant to heat, drought, and chemical damage. Phylogenomic analysis reveals a ubiquitous presence of the ena ‐gene cluster in the B. cereus group, which include species of clinical, environmental, and food importance. We propose Enas to represent a new class of pili specifically adapted to the harsh conditions encountered by bacterial spores. SYNOPSIS: Bacillus cereus sensu lato is a group of Gram‐positive human and animal pathogens forming endospores that are covered with abundant appendages of unknown identity. Here, cryo‐EM reconstruction uncovers the molecular identity of these ENdospore Appendages (Enas) and identifies them as a novel class of pili with unique architecture that combines high structural flexibility with resistance to environmental damage. Enas show two main morphologies: "Staggered" (S‐Ena) and "Ladder" (L‐Ena) type morphology. S‐Enas combine lateral ‐augmentation and longitudinal disulfide crosslinking to generate flexible, yet chemically hardy protein fibers. Ena subunits represent a conserved family of proteins encompassing the domain of unknown function DUF3992. Abstract : Cryo‐EM reconstruction reveals a novel class of pili in Gram‐positive bacteria, ENdospore Appendages (Enas), with a unique architecture and two distinct morphologies.